A review on renewable energy: Conversion and utilization of biomass - Xinping Yang; Yongjia Zhang; Peiliang Sun; Chong Peng (Smart Molecules)
Abstract The significant increase in demand for fuels and chemicals driven by global economic expansion has exacerbated concerns over fossil fuel consumption and environmental pollution. To achieve sustainable production of fuels and chemicals, biomass resources provide a rich repository for carbon‐neutral, green renewable energy, and organic carbon. This paper reviews the transformation and utilization of lignocellulosic biomass and its derivatives, emphasizing their valorization into high‐quality chemicals and biofuels. The advantages and disadvantages of various pretreatment methods are discussed based on the composition of lignocellulose. Furthermore, the methods and pathways for the valorization and conversion of cellulose, hemicellulose, and lignin are detailed according to the unique functional groups of different lignocellulosic platform molecules. However, the complex and resilient structure of biomass presents challenges for the disassembly and utilization of single components, and achieving high yields and selectivity for target products remains difficult. In conclusion, this paper comprehensively reviews the various types and pretreatment technologies of lignocellulose, focusing on the methods and pathways for the valorization of lignocellulosic biomass and its derivatives, thereby providing clear guidance and insights for optimizing lignocellulose utilization in the future.